Nomadic Firms in a Globalizing Economy: A Comparative Analysis and Policy Perspectives - Frank Bruinsma; Cees Gorter; Peter Nijkamp (Tinbergen Institute, 1998)
The location behaviour of modern multinational multi-plant firms appears to exhibitincreasingly a flexible mobility pattern with a strong tendency towards footlooseness. Thespatial-economic dynamics - often across the border - of such firms is sometimesencapsulated in the term 'nomadic firms'. This paper addresses the issue of nomadicbehaviour of firms against the background of globalisation trends. After a criticaldiscussion of globalisation phenomena and a review of the literature on nomadicentrepreneurial behaviour, the paper sets out to formulate a series of relevanthypotheses of spatial relocation behaviour of international firms in a globalisingnetwork economy.The analytical framework is tested by means of empirical dataoriginating from a field study among actual or potential nomadic firms, in bothThe Netherlands and abroad. Infrastructure quality and geographical accessibilityappear to play an important role in spatial relocation decisions, but also opportunityseeking behaviour of multinational firms has a prominent place in nomadic behaviour.The results of the structured interview rounds among various international firms arenext more rigorously analysed by using a recently developed method for qualitativeclassification and explanation, viz. rough set analysis. The results from the lattermethod confirm to a large extent our previous findings. The paper concludes with lessonsfor infrastructure policy.
Keywords: 330; Globalisierung; Betriebliche Standortwahl; Infrastruktur; Niederlande